Study on medicinal plants with special reference to family Asteraceae, Fabaceae and Solanaceae in G.G.V-Campus, Bilaspur (C. G.) in central India. - Patel, D K (Current Botany, 2012)
Present study deals with the study on mportant Medicinal plants diversity and documentation in G. G. V. – (A Central University) Bilaspur (C. G.). Many of the Medicinal plants have been recorded. Out of them a total number 36 species belonging to the family Asteraceae, Fabaceae and Solanaceae were listed. 10 species of Asteraceae, 17 species of family Fabaceae and 09 species of Solanacceae were observed. Highest percentage distribution of the plants shown by the family Fabaceae, whereas among three targeted families Solanaceae registered minimum % distribution in the university campus. After survey of area Medicinal plants were collected and categorized based on their related family and further scientific informations like Botanical name, Family, Habit, Parts used, Phyto-chemicals, Use and Propagation were noticed following literatures. The recorded data on Medicinal flora are listed in Tables and discussed furthermore.